A influência litoestrutural no surgimento e estruturação da rede de drenagem em rochas quartzíticas no Espinhaço Meridional /MG - Mateus Afonso Ramos (2016)
A river channel is an important relief shaping agent. Thus, understanding its genesis and structuring over time has become a key point in several geomorphological research. However, its relationship with the lithostructure is often unclear and little addressed in relief investigations. The drainage system are an extremely relevant factor on shaping the relief and, also generating sediments, especially in regions market by tectonic histories that affect all regional landscape evolution. Therefore, they are vital importance to understand the patterns of shapes and the impact on the setting of these geomorphological domains. This is the case for Espinhaço Meridional (SdEM), the great watershed of three of the main basins of Minas Gerais: São Francisco; Jequitinhonha and Doce – they provide a landscape overtaken by features inherited from tectonic events, in an early geological stage. The main purpose of this paper is to better understand the relationship between the development and structuring of the drainage network and the lithostructural characteristics of part of this massif, predominantly formed by silicytic rocks. It was given special emphasis on the study of headwaters with scattered drainage, which does not show clear structure of their waterways. Initially, the directions of the main structural lineaments and headwaters evolution axes were measured, based on the Pardo and Jequitinhonha basins and the various geological formations of the Espinhaço Supergroup. Diffuse drainage headwaters were mapped, seeking to identify lithostructural patterns for their emergence. Based on the aforementioned characteristics and their regional representativeness, identified by photo-aerial analysis (1:25.000), two headwaters of two drainage systems were chosen - the Pé de Moleque stream, located in the Pardo river basin, and the Ribeirão das Pedras, in Alto Jequitinhonha - in order to identify relationships between surface coverage and hydrological behavior. The exfiltration points were found in the two sample areas, which were characterized according to their morphology and type of exfiltration. It was possible, even in the field, to establish the relationship between the structural characteristics of the rocks and the flow direction formed at from the exfiltration points. The morphology of the headland areas was measured by topographic profiles made from the highest part, in contact with quartzite rocky outcrops, to the bottom of the depression, where precipitation water and the water table accumulate. Electroresistivity cross-sections were also performed to understand the subsurface dynamics of water in depression. The results showed that the evolution axis of the drainage headlands correlated with the direction of the main lineaments of the studied area, more prominent in the Pardo’s basin. The highest correlations were found in the drainages of the Galho do Miguel, Sopa-Brumadinho and Córrego do Pereira Formations. Most of the scattered headwaters are in the Pardo River basin, situated at elevations between 1,100 and 1,400 m and associated with syncline-anticline sequences and normal faults. In the sample areas, the surface coverings showed a close relationship with the source material and the exfiltration points have lithological influence on their appearance. Differences in the water dynamics of the two areas are noted since then. And while in the Pé de Moleque stream the runoff is controlled by the saturation runoff process and by the hortonian model, in the Pedras stream, the water flow is more controlled by the throughflow and baseflow process.